Wear behaviour and cutting performance of surfaced inserts for wood machining - Bendikiene, Regita (Strojniški vestnik, 2015)
Machining, in general, and wood machining, in particular, are complex to explain and many factors influence the process. Natural wood is a nonhomogeneous biological material, so each species of wood requires different machining conditions and tools. Understanding the properties of wood and choosing the proper cutting tools and machining parameters can improve the quality of wooden products, increase production efficiency, and improve machining. The objective of this study was to find the most suitable cutting tools for the machining of oak wood grown in Lithuania. This paper describes tests of two commercial cutting inserts made of high speed tool steel (CT01M-LA2 and 8X6FT) and two experimental inserts (EI) made by surfacing using a submerged arc welding (SAW) technique and a mixture of alloying elements spread on the surface under industrial flux. The results obtained from the milling tests demonstrated the suitability of the suggested surfaced inserts for machining oak wood. All tool wear parameters, such as cutting edge radius, edge recession, nose width, and cutting power, have been evaluated and compared. The cutting edge radius of EI after 3200 m of cutting length was ~ 5.00 %m, 3 to 4 times lower than the wear of standard tools; similarly, the edge recession of the surfaced inserts showed 2 to 3 times lower results. The results of this study indicate that the cutting power increases as the feed per cutter increases. These findings suggest that surfaced inserts can replace the commercial inserts used for wood machining.
Keywords: hrast (les); navarjanje; obraba orodja; obraba robu; rezkanje lesa; SAW